A GIANT PHYLLODES TUMOR: А CASE REPORT AND LITERATURE OVERVIEW - Inić, Zorka; Žegarac, Milan; Chia, Clement Luck Khng; Živković, Ognjen; Buta , Marko; Končar, Jovana; Marković, Ivan (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Phyllodes tumors of the breast are extremely uncommon, both in Serbia and worldwide. Identifying and treating these tumors can be challenging and they often represent a dilemma in diagnosis and treatment. Case report: We are presenting the case of a 60-year-old female with a large breast tumor that she had had for 15 years. According to the histopathologic diagnosis, it is a borderline phyllodes tumor measuring 18x17x7 cm and weighing 4.6 kg. Conclusion: An accurate preoperative diagnosis and proper management of borderline phyllodes tumors are crucial for successful surgery and for avoiding any further surgeries. This secondary prevention is critical because phyllodes tumors often recur and have malignant potential.